Thermocouples Technology and Applications A review - A. Osman, Abdalla; baidi, Abdulrasoul J. Alzu; M. Abdelrahman, Ali (Gezira Journal of Engineering and Applied Sciences, 2007)
This paper gives an intensive survey of thermocouples. In particular, it describes the principles of operation and compares between different types of junctions. It provides the major advances in thermocouples in conjunction with hardware and software for PC interfacing. Also it summarizes the main advantages and disadvantages of thermocouples. Finally the paper highlights the important areas of industrial applications.